Urban design policies implementation in Kuala Lumpur City Hall Malaysia: a review - Hussin, Natasha Azim; Mohd. Hussain, Mohd. Ramzi (Otago Polytechnic, 2025)
Urban Design Policies (UDPs) play a vital role in shaping the spatial form, functionality, and identity of contemporary cities. In Kuala Lumpur, these policies are embedded in key planning documents such as the Kuala Lumpur Structure Plan 2020 (PSKL2020), Urban Design Guidelines for Kuala Lumpur City Centre (UDGKLCC) 2014, Kuala Lumpur Structure Plan 2040 (KLSP2040) and Kuala Lumpur Local Plan 2040 (KLLP2040). These policies aim to enhance livability, promote walk ability and strengthen the city’s visual and spatial character. However, despite their comprehensive objectives, the outcomes of implementation have been inconsistent, raising questions about policy effectiveness and the factors that influence successful execution. Despite their comprehensive objectives, implementation outcomes have been inconsistent, raising questions about policy effectiveness and the successful execution. This paper critically reviews the literature on the effectiveness of UDP implementation with a particular focus on Kuala Lumpur. The review encompasses discussions on urban design concepts, urban design policies, the notion of effective implementation and the current status of UDP implementation in Kuala Lumpur. In this regard, this paper discusses the effective implementation of urban design policies in Kuala Lumpur with a particular focus on their execution by Kuala Lumpur City Hall (KLCH) as the local authority.